The Effect of Online Learning on The Social Competence of Early Childhood Teachers - Apriliani Diah; Saba Qadhi (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
This study examines the effect of online learning on the social competence of early childhood teachers, focusing on communication skills, collaboration, emotional regulation, and interactions with children and parents. Using a qualitative approach, data were collected through interviews, observations, and documentation from teachers engaged in online professional learning and instructional activities. The findings reveal that online learning provides meaningful opportunities for professional networking, knowledge sharing, and reflective dialogue, which contribute positively to teachers’ communication confidence and collaborative attitudes. However, the transition to digital platforms also reduced informal social interactions and limited the depth of relational connection among teachers, parents, and children. Teachers reported challenges in interpreting emotional cues, sustaining engagement, and building strong interpersonal bonds in virtual environments. The study further shows that the impact of online learning is context-dependent, influenced by technological access, institutional support, and digital literacy levels. Despite initial stress and uncertainty, teachers gradually developed resilience and adaptability in managing online communication. Overall, the results indicate that online learning both enhances and constrains social competence, suggesting the need for balanced integration of digital and face-to-face professional development. Strengthening institutional support and digital communication training is essential to maximize the benefits of online learning for teacher social competence.